Comparative investigations on pilot-scale anaerobic digestion of food waste at 30°C and 35°C - Long, Wang; Baoning, Zhu; Hairong, Yuan; Yanping, Liu; Dexun, Zou; Xiujin, Li (International Journal of Agricultural and Biological Engineering, 2016)
Parallel pilot-scale anaerobic digestion systems were conducted to evaluate the influence of system temperatures (30°C and 35°C) on digestion performance, greenhouse gas control and economic efficiency. Biogas productions (6.64- 12.96 m3/d) and methane yields (0.46-0.61 m3/kg VS) of 35°C digestion system were significantly higher than those of 30°C digestion system with the organic loading rate (OLR) of 2.0-4.5 kg VS/m3•d. Two regression equations of methane yields with increasing OLRs were fitted at 30°C and 35°C to predict the methane production of practical food waste (FW) digestion plants. By analyzing process stability, the optimal operating OLRs of 35°C digestion system (4.0 kg VS/m3•d) was found to be higher than that of 30°C digestion system (3.0 kg VS/m3•d), indicating that the 35°C digestion system had better processing capacity. The greenhouse gas emission under corresponding optimal operating OLR of 35°C digestion system was also calculated to be better than that of 30°C digestion system. Even the system temperature of 30°C was found to be more suitable for the digestion where OLR was less than 3.0 kg VS/m3•d, a higher operational temperature of 35°C was still a better choice for conventional high-solid digestion.Keywords: food waste, anaerobic digestion, pilot-scale, organic loading rate, greenhouse gas, economic efficiencyDOI: 10.3965/j.ijabe.20160901.1748Citation: Wang L, Zhu B N, Yuan H R, Liu Y P, Zou D X, Li X J. Comparative investigations on pilot-scale anaerobic digestion of food waste at 30°C and 35°C. Int J Agric & Biol Eng, 2016; 9(1): 109-1187.